2012
DOI: 10.1371/journal.pone.0049463
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Novel and Differentially Expressed MicroRNAs of Dairy Goat Mammary Gland Tissues Using Solexa Sequencing and Bioinformatics

Abstract: MicroRNAs are small, noncoding RNA molecules that regulate gene expression at the post-transcriptional level and play an important role in various biological processes. Although most microRNAs expression profiles studies have been performed in humans or rodents, relatively limited knowledge also exists in other mammalian species. The identification of the full repertoire of microRNAs expressed in the lactating mammary gland of Capra hircus would significantly increase our understanding of the physiology of lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 61 publications
4
68
0
1
Order By: Relevance
“…A similar study has been presented by Ji et al (29). The authors identified novel and differentially expressed microRNAs of dairy goat mammary gland tissues.…”
Section: Biogenesissupporting
confidence: 72%
“…A similar study has been presented by Ji et al (29). The authors identified novel and differentially expressed microRNAs of dairy goat mammary gland tissues.…”
Section: Biogenesissupporting
confidence: 72%
“…The dysregulation of miR-143 is implicated in a wide range of malignancies, including various forms of lymphoma, carcinomas of the breast, lung and pancreas and cervical cancer (Tripathi et al 2009;Liu et al 2012;Kapoor 2014). Although miR-143 has been extensively investigated in a variety of pathological tissues, but its specific functions in mammary gland development, lactation and involution remain elusive, and according to our previous studies, miR-143 seemed to be an interesting candidate for involvement in mammary gland development, lactation and involution (Ji et al 2012a(Ji et al , 2012b. In this study, MTT and cell count were used to test the functions of miR-143 on proliferation and viability of dairy goat mammary epithelia cells.…”
Section: Discussionmentioning
confidence: 90%
“…The miR-143 sequence was predicted in our previous studies of the miRNA expression profiles of dairy goat mammary gland tissues based on Illumina/Solexa highthroughput sequencing technology deposited in miRBase (Ji et al 2012a(Ji et al , 2012b. Multiple studies have shown that miR-143 is linked to the regulation of a diverse set of processes in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Geng et al [130] compared skin mRNA expression at different hair follicle developmental stages (i.e., anagen, catagen, and telogen), thus identifying hundreds of differentially expressed genes. There has also been a sudden burst of studies analysing the expression profiles of miRNAs in the mammary gland [132][133][134][135], testis [136], and skin and hair follicles [137]. Interestingly, overexpression of caprine miR-103 in cultured mammary epithelial cells has been shown to have broad effects on lipid metabolism [135], stimulating the expression of genes related with lipogenesis, unsaturated fatty acid synthesis, triglyceride synthesis, cholesterol transport, fatty acid uptake, and fat droplet formation and downregulating those involved in lipid catabolism (lipolysis and fatty acid -oxidation).…”
Section: New Tools For Analysing the Goat Genome And Transcriptomementioning
confidence: 99%
“…The large-scale measurement of mRNA expression has been greatly facilitated by the development of next generation sequencing techniques, and it should play a crucial role in understanding how genetic polymorphisms and environmental factors modulate gene expression through complex biological networks that evolve in time and space. In this regard, genome sequencing and RNA-seq experiments have allowed to establish an initial catalog of the miRNA genes residing in the goat genome [103,[132][133][134][135][136][137], and in the next years we can anticipate that this list will be expanded to new miRNAs as well as to a plethora of regulatory RNAs, such as small interfering RNAs, Piwi-associated RNAs, and long noncoding RNAs, with significant effects on gene expression.…”
Section: Final Remarksmentioning
confidence: 99%